1966
DOI: 10.1161/01.cir.34.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Combined Clinical and Metabolic Study of the Effects of Alpha-Methyldopa on Hypertensive Patients

Abstract: ALPHA-METHYLDOPA (a-methyl-3,4-di-IA hydroxy-L-phenylalanine [Aldomet]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The mean features of the disposition and metabolism of a-methyldopa have been established in normal and hypertensive adults (Buhs, Beck, Speth, Smith, Trenner, Cannon & Laragh, 1964;Prescott, Buhs, Beattie, Speth, Trenner & Lasagna, 1966; Au, Dring, Grahame-Smith, Isaac & Williams, 1972;Kwan, Faltz, Breault, Baer & Totaro, 1976). The results of investigations conducted with radiolabelled a-methyldopa have shown that after intravenous dosage most of the administered radioactivity is excreted in the urine within 24 h and little excretion occurred beyond this time.…”
mentioning
confidence: 99%
“…The mean features of the disposition and metabolism of a-methyldopa have been established in normal and hypertensive adults (Buhs, Beck, Speth, Smith, Trenner, Cannon & Laragh, 1964;Prescott, Buhs, Beattie, Speth, Trenner & Lasagna, 1966; Au, Dring, Grahame-Smith, Isaac & Williams, 1972;Kwan, Faltz, Breault, Baer & Totaro, 1976). The results of investigations conducted with radiolabelled a-methyldopa have shown that after intravenous dosage most of the administered radioactivity is excreted in the urine within 24 h and little excretion occurred beyond this time.…”
mentioning
confidence: 99%
“…4), strongly suggest that these O-methylated metabolites are not physiologically inert. Prescott et al (1966) noted a 40% increase in the…”
Section: Discussionmentioning
confidence: 97%
“…Prescott et al (1966) observed that hypertensive patients taking AMD for 1 month have a 40% increase in the percentage excreted as 3-O-methyl-methyldopa (OMMD), compared with amounts excreted after a single dose. These authors also noted a direct linear correlation between the antihypertensive effect of AMD and the 24-hour urinary excretion of OMMD in chronically treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By competitively inhibiting the sympathetic effects of norepinephrine, it decreases systemic arterial pressures and also decreases plasma renin activity. 3 Both methyldopa and a-methyl norepinephrine are renally excreted. 4 In adults with normal renal function (glomerular filtration rate: 90-120 mL/min), elimination is completed in 24 to 48 hours and rebound effects from chronic therapy have been reported within 48 hours, most prominently manifested by tachycardia and hypertension.…”
Section: Discussionmentioning
confidence: 99%